2009
DOI: 10.1590/s1678-77572009000700019
|View full text |Cite
|
Sign up to set email alerts
|

The implementation and preliminary evaluation of an ART strategy in Mexico: a country example

Abstract: The massive use of preventive measures in Mexico including fluoride toothpaste, a national program of salt fluoridation and education on prevention has resulted in a large decline in dental caries over the past two decades. There does however remain a largely unmet need for restorative treatment. This paper describes the steps leading up to the adoption of a strategy, as part of general health policy, to use Atraumatic Restorative Treatment (ART) within the Mexican public health service as a means to address t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 5 publications
0
20
0
4
Order By: Relevance
“…The major problem experienced by 45% of the respondents was found to be the scarcity or unavailability of appropriate dental materials and the lack of suitable instruments; those that were available being of poor quality [1]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major problem experienced by 45% of the respondents was found to be the scarcity or unavailability of appropriate dental materials and the lack of suitable instruments; those that were available being of poor quality [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Between 1989 and 2001, the mean DMFT score among 12-year olds declined from 4.4 to 1.91. Of this, the decayed tooth component was 1.54, the missing teeth component 0.04, and the filled teeth component was 0.34 [ 1 ]. The prevalence of dental caries in schoolchildren aged 12 years was 58% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com este estudo, a introdução do ART nos serviços públicos de atenção odontológica em países latino-americanos ocorreu, mas ainda encontra-se em fase incipiente. No México, uma exceção à regra latino-americana, a adoção de uma estratégia que utiliza as restaurações atraumáticas no serviço público de saúde como alternativa para amenizar o problema da falta de acesso aos tratamentos restauradores tradicionais já é uma realidade bem sucedida (13). Para que isso ocorresse, foi necessário o desenvolvimento de materiais didáticos, a organização de cursos de formação para dentistas e a incorporação do ART nos currículos de graduação.…”
Section: Discussionunclassified
“…39 The reasons for this lack of care is obviously multifactorial but demands the question whether other models of delivery of oral care using approaches such as ART could be explored in France, for instance providing prevention and caries management within the schools as is done in other countries. 40 Likewise, non-mobile elderly or physically and mentally handicapped people might not easily be able to access the dental clinic. Although oral health data for the elderly in France is limited, a report by the Haute Autorité de Santé (HAS) showed that elderly people have little access to dental care and that between 30-60% require restorative treatment.…”
Section: Indications At the Patient Levelmentioning
confidence: 99%